2021
DOI: 10.1039/d0cc06983c
|View full text |Cite
|
Sign up to set email alerts
|

Electron transfer within β-diketiminato nickel bromide and cobaltocene redox couples activating CO2

Abstract: Even though β-diketiminato nickel(ii) bromide and cobaltocene have nearly identical redox potentials the corresponding electron transfer complex can be crystallised from the equilibrium and activates CO2 to form a mononuclear nickel(ii) carbonate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…In DMF, with 0.1M TBAPF6 as electrolyte, a reversible wave can be observed at Ep = -1.92 V vs Fc + /Fc which has previously been assigned to decamethylcobalticenium cation. 35 Confirmation of this assignment is given by the CV of [Cp*2Co]PF6 in DMF with identical results (Figure S37, overlay). The second reduction feature observed (assigned as the Re 1/0 couple) is ~300 mV cathodically shifted with Ep = -2.31 V vs Fc + /Fc, as might be expected from an anionic complex utilizing the amide donor atom.…”
Section: Resultssupporting
confidence: 65%
“…In DMF, with 0.1M TBAPF6 as electrolyte, a reversible wave can be observed at Ep = -1.92 V vs Fc + /Fc which has previously been assigned to decamethylcobalticenium cation. 35 Confirmation of this assignment is given by the CV of [Cp*2Co]PF6 in DMF with identical results (Figure S37, overlay). The second reduction feature observed (assigned as the Re 1/0 couple) is ~300 mV cathodically shifted with Ep = -2.31 V vs Fc + /Fc, as might be expected from an anionic complex utilizing the amide donor atom.…”
Section: Resultssupporting
confidence: 65%
“…The solid-state structure, shown in Figure 3 There is precedent for Ni-mediated reductive disproportionation of CO 2 to form CO and CO 3 2− . 31−33 Specifically, a Ni(I) complex supported by a β-diketiminate ligand was shown to react with CO 2 to form a Ni carbonate species and free CO. 33 Monitoring the reaction of eq 5 by 1 H NMR spectroscopy showed that 3 formed in approximately 50% yield. The corresponding CO−containing product was found to be [(IPr)Ni] 2 (μ-CO) (μ-η 2 η 2 -CO 2 ) 28 (4), observed in 32% yield by 1 H NMR spectroscopy.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…For comparison, the homoleptic zinc bis­(formazanate) complex L 2 Zn reported by Otten and co-workers in 2015 undergoes two ligand-based redox events at −1.80 and −2.30 V. Consequently, it is tempting to assign the redox event at E 1/2 = −1.12 V versus Fc +/0 for 1 to a Ni II /Ni I redox process [note that a iron­(II) bis­(formazanate) complex was found to undergo metal-centered reduction at a comparable potential]; however, studies on other heteroleptic transition-metal formazanate complexes have clearly shown that the LUMO of formazanate complexes is ligand-centered. , Hence, we also assign the process observed for 1 to a reversible ligand-centered reduction. For comparison, the Ni II /Ni I event of a β-diketiminatonickel­(II) bromide complex occurs at −1.37 V (vs Fc/Fc + ) …”
Section: Resultsmentioning
confidence: 99%
“…For comparison, the Ni II /Ni I event of a βdiketiminatonickel(II) bromide complex occurs at −1.37 V (vs Fc/Fc + ). 25 On this basis, subsequently the chemical reduction of 1 was investigated. First, complex 1 was reacted with 2 equiv of sodium naphthalenide at −78 °C in toluene for 1 h. The product turned out to be NMR-silent because of paramagnetism.…”
Section: ■ Results and Discussionmentioning
confidence: 99%